A Comparative Evaluation of the Stability of Four Processing Solutions (Champion, Cronex, Teifsaz, Novin) in Processing of Intraoral Films After Time Intervals - E - Hekmatian; M Mahdizadeh; GhR Rostami (Isfahan University of Medical Sciences, 2005)
Introduction. In order to obtain good radiographs having optimum processing solution is important. Generally after a period of time the solutions will be oxidized and loose their efficacy. The goal of present research is comparison of the quality stability of four processing solutions available in market "Champion, Teifsaz, Cronex and Novin".Methods and Materials. One hundred and twenty eight intraoral radiographic films of one type with specific speed were exposed under identical exposure factors. A metal step wedge was used for the image. Each 4 days two periapical films were exposed and processed this was continued for two months. Finally optical density of radiographs processed in each solution were measured and compared according to the day of investigation.Results. All of the four solutions created acceptable density on the radiographs on the first day but there was a decrease in optical density after a period of time. Generally the Champion solution made the best density and after that were Cronex, Teifsaz and Novin. There was a decrease in the quality of Teifsaz, Cronex, Champion and Novin in order.Discussion. As the composition and percentage of these four solutions are different, the stability of them are also different. Champion was found to have the best quality among three other processing solutions.Key words. Processing solution, Quality, Stability, Champion, Teifsaz, Cronex, Novin.